PACER SHARE productivity and personnel management demonstration : first-year evaluation - Orvis, Bruce R.; Hosek, James R.; Mattock, Michael G., 1961-; Mazel, Rebecca M.; Bauman, R. L. (Roya L.); Rand eBooks (Santa Monica, CA : RAND, 1991)
This report describes the PACER SHARE Productivity and Personnel Management Demonstration, the plan that has been developed to evaluate it, and presents statistical results concerning the effects of the demonstration through its first year. PACER SHARE's purpose is to determine whether several experimental changes (job series consolidation, revised base pay determination, revised supervisory grading criteria, revised hiring/retention criteria, and productivity gainsharing) in federal civil service practices will improve organizational productivity, flexibility, and quality of work life while sustaining or improving the quality and timeliness of work. In these very preliminary, first-year results the authors did not find strong evidence of cost savings. In contrast, organizational flexibility improved, although the pattern was not universal across all measures. Attitudes toward pay and advancement declined while attitudes toward noneconomic aspects of the work environment changed equivalently or improved relative to the comparison sites. Work quality remained superior at Sacramento.
"National Defense Research Institute"--Cover.
This research "is being carried out by the Defense Manpower Research Center, a component of RAND's National Defense Research Institute"--Preface.
Includes bibliographical references (p. 107-110).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Sacramento Air Logistics Center -- Personnel management; Electronic books